Bentuk Perlindungan Hukum PPAT Penerima Protokol sebagai Turut Tergugat dalam Sengketa Akta di Pengadilan - Alifia Jasmine; Benny Djaja (Fakultas Hukum, Universitas Warmadewa, 2025)
This research examines the legal position and protection of Land Deed Officials (PPAT) receiving protocols in Indonesia's land law system. PPAT plays a vital role in creating and storing authentic land deeds. When a PPAT retires or passes away, the deed protocols must be transferred to a successor PPAT. However, in practice, PPAT receiving protocols often face legal disputes over deeds prepared by their predecessors, despite having no involvement in their creation. Using a normative juridical approach, this study analyzes relevant regulations and the case study of PN Medan Decision No. 254/Pdt.G/2023/PN Mdn. The findings reveal that the responsibility of PPAT receiving protocols should be purely administrative, limited to document storage rather than the substance of the deeds. Nevertheless, the lack of clear regulations creates legal uncertainty and leaves receiving PPAT vulnerable. Therefore, this study recommends enacting specific regulations to limit the liability of PPAT receiving protocols to administrative aspects only, along with establishing legal protection through professional organizations and related institutions to prevent injustice in handling legal disputes.